Comparing multiple models of educational interventions in patients with heart failure: preliminary results of the study MEETTinCy - Kalogirou, Fotini; Protopapas, A; Middleton, Nicos; Papathanassoglou, Elizabeth; Lamnisos, Demetris; Lambrinou, Ekaterini (My University, 2013)
The aim of the current work is to present the preliminary results of an ongoing randomized control trial. The study evaluates the effects of predischarge education and/ or telephone education and support, provided by a nurse, on HF patients’ QoL and self-care behaviors.
Keywords: Heart failure